Atrial flutter and fibrillation in patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension in the ASPIRE registry: Comparison of rate versus rhythm control approaches. (15th January 2023) - Sammut, Mark Anthony; Condliffe, Robin; Elliot, Charlie; Hameed, Abdul; Lewis, Robert; Kiely, David G.; Kyriacou, Andreas; Middleton, Jennifer T.; Raithatha, Ajay; Rothman, Alex; Thompson, A.A. Roger; Turner, Richard; et al.
Abstract: Background: The development of atrial flutter and fibrillation (AFL/AF) in patients with pre-capillary pulmonary hypertension has been associated with an increased risk of morbidity and mortality. Rate and rhythm control strategies have not been directly compared. Methods: Eighty-four patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH) with new-onset AFL/AF were identified in the ASPIRE registry. First, baseline characteristics and rates of sinus rhythm (SR) restoration of 3 arrhythmia management strategies (rate control, medical rhythm control and DC cardioversion, DCCV) in an early (2009–13) and later (2014–19) cohort were compared. Longer-term outcomes in patients who achieved SR versus those who did not were then explored. Results: Sixty (71%) patients had AFL and 24 (29%) AF. Eighteen (22%) patients underwent rate control, 22 (26%) medical rhythm control and 44 (52%) DCCV. SR was restored in 33% treated by rate control, 59% medical rhythm control and 95% DCCV ( p  < 0.001). Restoration of SR was associated with greater improvement in functional class (FC) and Incremental Shuttle Walk Distance (p both <0.05). It also independently predicted superior survival (3-year survival 62% vs 23% in those remaining in AFL/AF, p  < 0.0001). In addition, FC III/IV independently predicted higher mortality (HR 2.86, p  = 0.007). Right atrial area independently predicted AFL/AF recurrence (OR 1.08, p  = 0.01). DCCV was generally well tolerated with no immediate major complications. Conclusions: Restoration of SR is associated with superior functional improvement and survival in PAH/CTEPH compared with rate control. DCCV is generally safe and is more effective than medical therapy at achieving SR. Highlights: Atrial arrhythmias increase morbidity and mortality in pulmonary hypertension Restoration of sinus rhythm leads to improved functional status and survival DC cardioversion is a safe and effective initial strategy to achieve rhythm control